Pemanfaatan Supernatan Lactobacillus plantarum Sebagai Penghambat Pertumbuhan Escherichia coli pada Dangke Susu Sapi (UTILIZATION OF LACTOBACILLUS PLANTARUM SUPERNATAN AS AN INHIBITIOR OF ECHERICHIA COLI GROWTH IN COW’S MILK DANGKE - Arini, Nining; Sudarwanto, Mirnawati; Sudirman, Idwan; Indrawati, Agustin (Jurnal Veteriner; Vol 17 No 3 (2016), 2016)
Dangke is a traditional food in Enrekang, a district in South Sulawesi. Its made from buffalo’s milk orcow’s milk. Dangke could be contaminated during the process with Escherichia coli which causes diarrheain children and adults. It was known that supernatant of Lactobacillus plantarum has antibacterial capacity,and it may be used as a biopreservative agent. The research aims were to determine the minimum inhibitoryconcentration (MIC) of L. plantarum supernatant in inhibiting the growth of E. coli ATCC 25922, determinethe nutrients level of cow’s milk dangke after the addition of 1% and 2% milk fat, as well as determine theeffect of L. plantarum supernatant and cow’s milk fat addition into dangke inhibited the growths of pathogenicbacteria of E. coli ATCC 25922. MIC value was determined based on the value of the lowest concentrationof supernatant that shown with no any bacteria growth in the media. Data of pathogenic bacteria growth analyzed with analysis of variance test with a 2x2 factorial design, which 1st factor was the addition of L.plantarum supernatant (with or without addition of supernatant) and the second factor was the additionof fat content (1% and 2%) and time observation was made on days 0, 2nd, 4th, 6th, and 8th. Resultsshowed that the filtrate of fermented L. plantarum was able to inhibit the growth of E. coli ATCC 25922in vitro and had 10% minimum inhibitory concentration (MIC). Level of fat and protein in dangke whichadded 1% cow’s milk fat, was higher than with 2% cow’s milk fat. The L. plantarum supernatant is provedto be able to inhibit the growth of E. coli ATCC 25922. Therefore, it is potentially used as a naturalbiopreservative agent in making dangke.
Keywords: dangke; Lactobacillus plantarum supernatant; cow’s milk fat; E. coli ATCC 25922